DESENTRALISASI SEBAGAI VARIABEL PEMODERASI HUBUNGAN ANTARA PARTISIPASI ANGGARAN TERHADAP KINERJA APARATUR PEMERINTAH DAERAH PROVINSI SULAWESI TENGAH - Munayang, Olivia H.; Fitriana, Fitriana (Jurnal Akun Nabelo : Jurnal Akuntansi Netral, Akuntabel, Objektif, 2019)
This research uses accounting science approach, especially public sector accounting. This study aims to examine the relationship between budgetary participation on apparatus performance by using decentralization as a moderating variable. The sampling method uses saturated or census sampling method. Analysis of the data used is moderating regression analysis. The data obtained from the results of giving questionnaires and direct interviews with respondents as many as 66 people. The results of this study indicate a significance value of 0.184>0.05, so budget participation does not affect the performance of the apparatus. And the significance value of the interaction test is 0.438>0.05, so budget participation does not affect the performance of the apparatus which is moderated by decentralization.